Caspase Inhibition During Cold Storage Improves Graft Function and Histology in a Murine Kidney Transplant Model. Issue 9 (September 2018) - Nydam, Trevor L.; Plenter, Robert; Jain, Swati; Lucia, Scott; Jani, Alkesh
Abstract : Background: Prolonged cold ischemia is a risk factor for delayed graft function of kidney transplants, and is associated with caspase-3–mediated apoptotic tubular cell death. We hypothesized that treatment of tubular cells and donor kidneys during cold storage with a caspase inhibitor before transplant would reduce tubular cell apoptosis and improve kidney function after transplant. Methods: Mouse tubular cells were incubated with either dimethyl sulfoxide (DMSO) or Q-VD-OPh during cold storage in saline followed by rewarming in normal media. For in vivo studies, donor kidneys from C57BL/6 mice were perfused with cold saline, DMSO (vehicle), or QVD-OPh. Donor kidneys were then recovered, stored at 4°C for 60 minutes, and transplanted into syngeneic C57BL/6 recipients. Results: Tubular cells treated with a caspase inhibitor had significantly reduced capsase-3 protein expression, caspase-3 activity, and apoptotic cell death compared with saline or DMSO (vehicle) in a dose-dependent manner. Treatment of donor kidneys with a caspase inhibitor significantly reduced serum creatinine and resulted in significantly less tubular cell apoptosis, BBI, tubular injury, cast formation, and tubule lumen dilation compared with DMSO and saline-treated kidneys. Conclusions: Caspase inhibition resulted in decreased tubular cell apoptosis and improved renal function after transplantation. Caspase inhibition may be a useful strategy to prevent cold ischemic injury of donor renal grafts. Abstract : The authors investigate the efficacy of caspase inhibitor on improvement of graft function and attenuation of tubular cell apoptosis in a mouse kidney transplantation model (in vivo) as well as mouse tubular cells (in vitro). Supplemental digital content is available in the text.